EPHX2 overexpression deters the advancement of clear cell renal cell carcinoma via lipid metabolism reprogramming - Guan, Bo; Huang, Cong; He, Jun; Shan, Weimin; Cui, Di; Li, Xiaowei; Liang, Chaozhao; Hao, Zongyao (Frontiers in Oncology, 2025)
BackgroundClear cell renal cell carcinoma (ccRCC) is a prevalent and highly aggressive subtype of renal cancer. EPHX2, a metabolic regulator with tumor-suppressive properties, not only influences cell cycle dynamics but also interacts with multiple signaling pathways to inhibit tumor growth. However, the specific mechanistic role of EPHX2 in tumorigenesis remains largely unexplored.ObjectiveTo elucidate the mechanistic role of EPHX2 in the progression of ccRCC. MethodsBulk transcriptome data, single-cell transcriptome data, and gene set data for ccRCC were sourced from the TCGA database and GEO database. An integrated machine learning approach was employed, utilizing the TCGA dataset as the training set and the MTAB dataset as the test set, to develop prognostic models. Subsequently, EPHX2 was stably overexpressed in the 786-O and ACHN cell lines via lentiviral transfection technology, and its functional effects were validated through in vitro experiments. ResultsThrough ADIPOGENESIS gene set scoring and differential expression analysis, ten key genes, including EPHX2, were identified. Notably, EPHX2 expression was significantly lower in ccRCC tumor tissues compared to normal renal tissues (P < 0.001). Furthermore, overexpression of EPHX2 significantly inhibited the proliferative, migratory, and invasive capacities of ccRCC cell lines. ConclusionEPHX2 plays a pivotal role in the pathophysiological processes of ccRCC, suggesting its potential as a therapeutic target and prognostic biomarker.